ANALISIS PENGARUH TRANSFORMATIONAL LEADERSHIP TERHADAP DEVIANT BEHAVIOR IN WORKPLACE: JOB SATISFACTION SEBAGAI VARIABLE MEDIASI - Rizki Nofriadi; Zaitul Zaitul; Reni Yuliviona; Listiana Sri Mulatsih; Yurizal Yurizal (Universitas Bina Taruna Gorontalo, 2024)
This research aims to analyze the influencetransformational leadership todeviant behaviorworkplace. In addition, this research also investigates the rolejob satisfaction as an intermediate mediating variabletransformational leadership anddeviant behavior at workplace. The object of the research is employees who work at the Teluk Bayur Type A Class II Navigation District Office. Research data is primary data collected using a survey method of 35 respondents by completely filling in the questionnaire distributed. The analysis method uses Structural Equation Model (SEM) withsoftware Smart-PLS 3. The theory used is the theory of transformational leadership, deviant behavior, and job satisfaction. The research results show that four statements are valid for the variablestransformational leadership andjob satisfaction. Meanwhile variablesdeviant behavior at work has five valid statement items. The results of the hypothesis test show that the influencetransformational leadership todeviant behavior in the workplace is not directly evident. However, indirectly, it is a relationshiptransformational leadership anddeviant behavior in workplace mediated byjob satisfaction. The study results have theoretical and practical implications.